Konsep Masjid Ramah Anak Dalam Pandangan Badan Kemakmuran Masjid (BKM) - Rustam Pakpahan (Universitas Islam Negeri Sumatera Utara, 2018)
Since the introduction of child-friendly in 1990, the concept has been widespread in some aspects of people’s life. The concepts of child-friendly school, child-friendly space, and child-friendly city have been more popular. However, the concept of child-friendly has not much so far related to houses of worship. The present research aims at exploring how the caretakers of mosques perceive the concept of child-friendly mosque. The study suggests that children are subject to physical and verbal violence in the mosque. In addition, many mosques are also not convenient for children due to the policies and physical structures of the mosques which are not child friendly, and the absence of facilities designed for the best interest of the child. The mosque caretakers are aware of the messages in Islamic teaching to protect the children and behave softly to them. However, violence continues.